Pengetahuan dan Pendapat Mahasiswa Poltekkes Surabaya Tentang Kelainan Genetik dan Skrining Pra-Nikah - Wulandari, Retno Dwi; Setijowati, Eva Diah (Journal of Community Development, 2024)
To ensure couples planning to get married understand the genetic risks related with their future offspring, they need to acquire information about genetic disorders and pre-marital genetic counselling that can be followed by genetic screening. Genetic disorders can be inherited from normal parents who are carriers of abnormal genes, such as thalassemia and Haemophilia. Genetic disorder also encompass chromosomal abnormalities, either the number or structure chromosome. Unlike numerical chromosomal abnormalities in offspring, which have an increased risk associated with the mother’s age during pregnancy, structural abnormalities in parents can be passed to their offspring. This community service activity targets seventh-semester students at Poltekkes Kemenkes Surabaya, who are at an age ready for marriage. The implementation of this activity begins with a pre-test to assess the student ‘s knowledge before the education presentation, followed by presentation with interactive discussion and ended with post-test to determine whether the education was comprehensible to them. Poltekkes Kemenkes Surabaya students showed a better understanding of genetic disorder indicated with an average score increase of 8.2 points (9.2%) based on post test result . All students agree on the importance of pre-marital screening, with the majority willing to undergo premarital screening and still proceed with the marriage if their partner is a carrier of thalassemia.